The influence of social media, digitalization, and financial literacy on generation Z's investment decision - Daulay, Muthia Aulia Azhari; Marliyah, Marliyah; Silalahi, Purnama Ramadani (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
The study aimed to understand how social media, digitalization, and financial literacy influence Sharia stock investment decisions among Generation Z. As Gen Z becomes more predominant, it presents both opportunities and challenges for transforming the digital landscape, particularly in terms of financial literacy and the distribution of products and services in the Sharia stock market. Data was collected through questionnaires distributed to 100 selected respondents using purposive sampling. A quantitative method was employed, utilizing the Structural Equation Model (SEM) with the Smart PLS application for analysis. The findings revealed that social media and digitalization significantly and positively influenced Sharia stock investment decisions among Generation Z. However, the financial literacy did not show a significant impact. Public interest statements The positive impact of social media and digitalization on investment decisions indicates that financial institutions and Sharia-compliant stock market participants should leverage these platforms to connect with Generation Z. Note: Early Version articles are published as standalone pieces and will later be compiled into issues prior to print publication. These Early Version articles will not appear in journal keyword searches, will not be included in article searches, and will not receive a DOI (Digital Object Identifier) until they are officially published in an issue.